Increase from low to moderate, but not high, caffeinated coffee consumption is associated with favorable changes in body fat. Issue 4 (April 2023) - Henn, Matthias; Babio, Nancy; Romaguera, Dora; Vázquez-Ruiz, Zenaida; Konieczna, Jadwiga; Vioque, Jesús; Torres-Collado, Laura; Razquin, Cristina; Buil-Cosiales, Pilar; Fitó, Montserrat; Schröder, Helmut; Hu, Frank B.; et al.
Summary: Background & aims: Higher consumption of coffee and caffeine has been linked to less weight gain and lower body mass index in prospective cohort studies. The aim of the study was to longitudinally assess the association of changes in coffee and caffeine intake with changes in fat tissue, in particular, visceral adipose tissue (VAT) using dual x-ray absorptiometry (DXA). Methods: In the setting of a large, randomized trial of Mediterranean diet and physical activity intervention, we evaluated 1483 participants with metabolic syndrome (MetS). Repeated measurements of coffee consumption from validated food frequency questionnaires (FFQ) and DXA measurements of adipose tissue were collected at baseline, 6 months, 12 months and 3 years of follow-up. DXA-derived measurements of total and regional adipose tissue expressed as % of total body weight were transformed into sex-specific z-scores. Linear multilevel mixed-effect models were used to investigate the relationship between changes in coffee consumption and corresponding concurrent changes in fat tissue during a 3-year follow-up. Results: After adjustment for intervention group, and other potential confounders, an increase in caffeinated coffee consumption from no or infrequent consumption (≤3 cups/month) to moderate consumption (1–7 cups/week) was associated with reductions in total body fat (Δ z-score: −0.06; 95% CI: −0.11 to −0.02), trunk fat (Δ z-score: −0.07; 95% CI: −0.12 to −0.02), and VAT (Δ z-score: −0.07; 95% CI: −0.13 to −0.01). Neither changes from no or infrequent consumption to high levels of caffeinated coffee consumption (>1 cup/day) nor any changes in decaffeinated coffee consumption showed significant associations with changes in DXA measures. Conclusions: Moderate changes in the consumption of caffeinated coffee, but not changes to high consumption, were associated with reductions in total body fat, trunk fat and VAT in a Mediterranean cohort with MetS. Decaffeinated coffee was not linked to adiposity indicators. Moderate consumption of caffeinated coffee may be part of a weight management strategy. Trial registration: The trial was registered at the International Standard Randomized Controlled Trial (ISRCTN: http://www.isrctn.com/ISRCTN89898870) with number 89898870 and registration date of 24 July 2014, retrospectively registered.